The utilization of the large unstained cell (LUC) parameter in lymphoid, haematopoietic and related tissue’s malignant neoplasms - Gök, Gamze; Erdoğan, Serpil; Asutay, Erbay; Yılmaz, Gülsen; Erel, Özcan; Yılmaz, Fatma Meriç (The European Research Journal, 2025)
Objectives: Large unstained cells (LUCs) are a differential count parameter reported by routine hematology analysis, and LUC percentages (LUC%) reflect active lymphocytes and peroxidase-negative cells. We aimed the evaluate the LUC% parameter in routine practice towards malignant neoplasms, stated or presumed to be primary, of lymphoid, haematopoietic, and related tissue. Methods: LUC analysis was performed with Siemens ADVIA® 2120 Hematology System. Data were obtained from Ankara Bilkent City Hospital’s laboratory information system. Results: A statistical difference in the LUC % data in the case of LUC %